A new coumarin derivative from the stems of the endangered plant Ulmus elongata. Issue 21 (2nd November 2021) - Zhou, Qi; Wu, Shou-Yuan; Jiang, Chun-Xiao; Tong, Ying-Peng; Zhao, Ting; Zhang, Bin; Nong, Xu-Hua; Jin, Ze-Xin; Hu, Jin-Feng
Abstract: A preliminary phytochemical investigation of the stems of the endangered plant Ulmus elongata led to the isolation of a new coumarin derivative (named ulmuselactone A, 1 ) and eight known compounds (2 -9 ). The new structure was elucidated by detailed analysis of comprehensive spectroscopic methods, and its absolute configuration was established by comparing experimental and calculated electronic circular dichroism (ECD) spectra. The isolated compounds were evaluated for their antibacterial activities. Graphical Abstract: